Hidden diversity of the widespread Opsaridium ubangiense (Cypriniformes: Danionidae) in Central Africa - Schmidt, Ray C.; Clements, Michael A.; Hinson, Madison W.; Barrientos, Christian (Zootaxa, 2025)
Opsaridium ubangiense is a reportedly widespread species that occurs throughout the Lower Guinea ichthyofaunal province and within the Upper Congo River drainage. Recent collections throughout the region allow us to examine the genetic diversity within this species across its reported distribution. The results of a multi-locus analyses and four different species delimitation methods (GD, bPTP, ABGD, and ASAP) suggest the presence of distinct taxa within what is now considered O. ubangiense. The analysis also revealed potentially distinct taxa within the rivers of Equatorial Guinea and highlight some interesting patterns of diversity within the Mbini River drainage. A preliminary morphological analysis also revealed some differences among topotypic material and other studied populations. These results are discussed in the context of other recent discoveries in the region; future studies needed are also detailed.